Bacterial inactivation, photoreactivation and dark repair post flow-through pulsed UV disinfection. (June 2021) - Fitzhenry, Kelly; Clifford, Eoghan; Rowan, Neil; Val del Rio, Angeles
Abstract: Pulsed UV (PUV) technology is accepted commercially for disinfection within the food packaging industry, but has yet to be deployed by the water/wastewater sector. This is partly due to a lack of robust, independently validated data for submerged or flow-through treatment applications. This study evaluated the efficacy of PUV for water disinfection under flow-through conditions. Bacterial pathogens of interest in the food and water/wastewater sector, namely Escherichia coli, Staphylococcus aureus and Listeria innocua (surrogate for L. monocytogenes ) were used to investigate the potential for photoreactivation and/or dark repair post PUV flow-through disinfection. A continuous-flow low-pressure UV was also analysed under similar experimental conditions. Bacterial inactivation via flow-through PUV was dependant on energy output with E. coli exhibiting greatest sensitivity to PUV treatment (5.3 log 10 inactivation after treatment at 1539 mJ/cm 2 - output in UV range < 300 nm); L. innocua exhibited the highest PUV resistance (3.0 log 10 inactivation after treatment at 1539 mJ/cm 2 – output in UV range < 300 nm) under similar treatment conditions. Greater photoreactivation occurred at lower PUV outputs for both S. aureus and E. coli after flow-through PUV treatment. Thus exposure of treated bacteria to natural light, immediately post flow-through PUV treatment, should be avoided to minimise photoreactivation. The LPUV demonstrated inactivation of all bacteria below the limit of detection (1 CFU/mL) and inhibited the occurrence of photoreactivation. This study highlights the importance of considering bacterial repair potential and the need for further development of PUV technology for such applications.